Needle to needle robot‐assisted manufacture of cell therapy products - Jelena Ochs; Mariana P. Hanga; Georgina Shaw; Niamh Duffy; Michael Kulik; Nokilaj Tissin; Daniel Reibert; Ferdinand Biermann; Panagiota Moutsatsou; Shibani Ratnayake; Alvin Nienow; Niels Koenig; et al. (Wiley, 2022)
Abstract Advanced therapeutic medicinal products (ATMPs) have emerged as novel therapies for untreatable diseases, generating the need for large volumes of high‐quality, clinically‐compliant GMP cells to replace costly, high‐risk and limited scale manual expansion processes. We present the design of a fully automated, robot‐assisted platform incorporating the use of multiliter stirred tank bioreactors for scalable production of adherent human stem cells. The design addresses a needle‐to‐needle closed process incorporating automated bone marrow collection, cell isolation, expansion, and collection into cryovials for patient delivery. AUTOSTEM, a modular, adaptable, fully closed system ensures no direct operator interaction with biological material; all commands are performed through a graphic interface. Seeding of source material, process monitoring, feeding, sampling, harvesting and cryopreservation are automated within the closed platform, comprising two clean room levels enabling both open and closed processes. A bioprocess based on human MSCs expanded on microcarriers was used for proof of concept. Utilizing equivalent culture parameters, the AUTOSTEM robot‐assisted platform successfully performed cell expansion at the liter scale, generating results comparable to manual production, while maintaining cell quality postprocessing.